Desquamative Plaques in the Skin Folds Unresponsive to Antifungal Medication: Diagnosis and Comment; [Placas Descamativas en Pliegues Que No Responden a Antimicóticos: Diagnóstico y Comentario] - Loubies-Muñoz, R; Aedo-Inostroza, G (Ediciones Doyma, S.L., 2023)
[No abstract available]